Contesting the Protestant Consensus: Voluntarists, Methodists, and the Persistence of Evangelical Dissent in Upper Canada, 1829-1854 - Forbes, James (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
This article challenges the premise that a Protestant consensus emerged in Upper Canada by the mid-nineteenth century by examining the persistence of politically influential, dissenting evangelical voluntarists who advocated the secularization of the clergy reserves. State- Chruch efforts were strongly contested by evangelicals who had come to believe that the purity of their faith was marked by its independence from the state as well as its revivalism. Using the Toronto-based Christian Guardian, this article traces a clash between the British Wesleyans and the generally voluntarist Upper Canadian Methodists as they sought to claim the legacy of Methodism in the colony. Overall, this article seeks to highlight the persistence of an early dissenting evangelical culture, not as an exception to the rule of consensus, but as a significant influence in colonial public policy and a vital force in Upper Canadian Protestantism that calls into question the consensus model.